Evaluation of the fulfillment grade and clinical management of the treatment with immunotherapy in allergic patients. - Marisela L. Pérez Pacaréu; Andrea Ortega Cabrera; Ania Sabina Díaz; Rafael Zamora Puerta (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2006)
Background: Immunotherapy efficacy in the control of patients affected by allergic diseases has been quite proved since 1911, it is of great importance for their betterment. Objectives: To determine the adherence to the treatment and patient´s satisfaction with control immunotherapy. Methods: A study made in the ¨Dr. Gustavo Aldereguia Lima¨ Hospital, where 100 patients from the external allergy consulter were evaluated for a year. Authorized personnel checked out the level of fulfilment of the security rules, clinical betterment was evaluated with a daily control of symptoms correlated with clinical history of allergy, and satisfaction was evaluated through a questionaire.Results: The 82% fits correctly with the treatment program, the 94% presented clinical betterment, and the 90% has an excellent satisfaction level.